Social support and associated factors among caregivers of elderly China: A cross-sectional study - Yun, Hu; Ji, Shen (Science Center Group, 2025)
Background: The rapid aging of the global population has increased the demand for long-term care, with family members often serving as primary caregivers for older adults. In China, cultural values such as filial piety strongly influence caregiving responsibilities, placing significant physical, emotional, and social demands on family caregivers. Social support has been identified as an important factor that may alleviate caregiving burden and improve caregiver well-being. Objective: This study aimed to assess perceived social support among family caregivers of older adults in China and to examine demographic factors associated with variations in social support. Methods: A descriptive cross-sectional study was conducted among 260 family caregivers of older adults aged 60 years and above in Jiangsu Province, China. Participants were recruited using convenience sampling from urban and rural communities. Data were collected using a structured questionnaire consisting of demographic characteristics and the Multidimensional Scale of Perceived Social Support (MSPSS). Descriptive statistics were used to summarize caregiver characteristics and levels of perceived support, while inferential analyses, including independent t-tests and one-way analysis of variance (ANOVA), were performed to identify demographic factors associated with perceived social support. Results: Caregivers reported the highest perceived social support from family members (M = 5.39), followed by significant others (M = 5.22) and friends (M = 4.88). Male caregivers reported significantly higher levels of perceived social support compared to female caregivers (p = 0.005). In addition, caregivers who had provided care for more than ten years reported significantly greater social support than those with shorter caregiving durations (p < 0.001). No significant associations were found between perceived social support and caregiver age, income, education, employment status, or caregiver training. Conclusion: Family remains the primary source of social support for caregivers of older adults in China. Gender and caregiving duration significantly influence perceived support levels. Strengthening community-based and peer support networks may help improve caregiver well-being and reduce caregiving burden